Mercury and Arctic Char Gill Microbiota Correlation in Canadian Arctic Communities - Flora Amill; Patrice Couture; Nicolas Derome (Microorganisms, 2024)
Arctic char is a top predator in Arctic waters and is threatened by mercury pollution in the context of changing climate. Gill microbiota is directly exposed to environmental xenobiotics and play a central role in immunity and fitness. Surprisingly, there is a lack of literature studying the effect of mercury on gill microbiota. To fill this knowledge gap, our primary goal was to measure to what extent gill exposure to mercury may alter gill microbiota activity in Arctic char. Specifically, we calculated the correlation between the taxonomic distribution of gill-associated bacterial symbiont activity and total mercury concentration in livers and muscles in wild populations of Arctic char in the Canadian Arctic. Our results showed that total mercury concentrations in tissues were higher in Ekaluktutiak (Nunavut) than in the other sites in Nunavik. Proteobacteria was the main phylum correlated to mercury concentration in both tissues, followed by Bacteroidetes and Cyanobacteria. In the most contaminated sites, Aeromonas and Pseudomonas (Proteobacteria) were predominant, while mercury concentration negatively correlated with Photobacterium (Proteobacteria) or Cerasicoccus (Verrucomicrobia). In summary, we found that mercury contamination correlates with active gill microbiota composition, with potential implications of strains in modulating mercury toxicity, making them interesting for future biomarker studies.